The bile acid metabolome in umbilical cord blood and meconium of healthy newborns: distinct characteristics and implications - Lu, Chunxia; Gao, Zhiyong; Zhang, Siqi; Du, Ke; Xu, Die; Dong, Wenbin; Zhang, Yujiao; Lei, Xiaoping (PeerJ (San Francisco, CA), 2024)
To characterize the bile acid metabolomic profiles of umbilical cord blood and meconium in healthy newborns. Fifteen healthy newborns, which born in the Obstetrics Department of the Affiliated Hospital of Southwest Medical University between July 1 and August 31, 2023, were selected as study subjects. Umbilical cord blood and meconium samples were collected, and bile acid metabolomics were analyzed using ultra-high performance liquid chromatography-tandem mass spectrometry. The ratio of primary to secondary bile acids in cord blood was significantly higher than in meconium [2.64 (2.49, 5.70) . 0.99 (0.37, 1.58), Z = -3.80, < 0.05]. The ratio of unconjugated to conjugated bile acids was notably higher in cord blood than in meconium [0.14 (0.07, 0.18) . 0.01 (0.01, 0.04), Z = -3.88, < 0.05]. The ratio of cholic acid to chenodeoxycholic acid in conjugated primary bile acids was significantly lower in cord blood than in meconium [0.59 (0.19, 0.75) . 2.21 (1.34, 3.04), Z = -4.21, < 0.05], but the ratio of cholic acid to chenodeoxycholic acid in secondary bile acids was significantly higher in cord blood than in meconium [0.42 (0.21, 0.63) . 0.03 (0.01, 0.05), Z = -4.54, < 0.05]. Only three primary bile acids (taurochenodeoxycholic acid, glycochenodeoxycholic acid, and glycochenodeoxycholic acid 3-glucoside in umbilical cord blood) were correlated with their downstream metabolites in meconium (with hyodesoxycholic acid (r = -0.66, = 0.01), tauro-ω-muricholic acid (r = 0.52, = 0.048) and ursodeoxycholic acid-7S (r = -0.53, = 0.04), respectively). In meconium, most of primary bile acids were correlated with their downstream metabolites ( all < 0.05): cholic acid was positively correlated with 3-dehydrocholic acid, taurocholic acid was positively correlated with taurodeoxycholic acid and 3-dehydrocholic acid, glycocholic acid was positively correlated with 3-dehydrocholic acid, chenodeoxycholic acid was positively correlated with glycoursodeoxycholic acid, taurolithocholic acid, and 7-keto lithocholic acid and negatively correlated with isolithocholic acid. Taurochenodeoxycholic acid was positively correlated with taurohyodeoxycholic acid, tauroursodeoxycholic acid, glycoursodeoxycholic acid, taurolithocholic acid, tauro-ω-muricholic acid, and glycohyodeoxycholic acid, while glycochenodeoxycholic acid was positively correlated with tauroursodeoxycholic acid, glycoursodeoxycholic acid, taurolithocholic acid, and glycohyodeoxycholic acid, and negatively correlated with isolithocholic acid. The bile acid metabolites in umbilical cord blood and meconium differ significantly, and the downstream bile acid metabolites in meconium are predominantly correlated with their upstream bile acids in meconium, but not those bile acids in umbilical cord blood. These findings contribute to a better understanding of bile acid metabolism and lay the foundation for future research in this topic.